2002
DOI: 10.1067/mhn.2002.127627
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lecithin on Mitochondrial DNA and Age‐Related Hearing Loss

Abstract: These experiments support our hypothesis and provide evidence that lecithin may preserve cochlear mitochondrial function and protect hearing loss associated with aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 15 publications
1
75
0
1
Order By: Relevance
“…SOD1 deficiency in mice induces cochlear hair cell degeneration and loss of spiral ganglion cells and nerve fibers, with ARHI as a consequence [McFadden et al, 1999a[McFadden et al, , b, 2001. Lecithin, a polyunsaturated phosphatidylcholine responsible for SOD activation, has a protective effect and preserves the hearing abilities in ageing subjects [Seidman et al, 2002b].…”
Section: Do Mitochondrial Mutations and Reactive Oxygen Species Contrmentioning
confidence: 99%
“…SOD1 deficiency in mice induces cochlear hair cell degeneration and loss of spiral ganglion cells and nerve fibers, with ARHI as a consequence [McFadden et al, 1999a[McFadden et al, , b, 2001. Lecithin, a polyunsaturated phosphatidylcholine responsible for SOD activation, has a protective effect and preserves the hearing abilities in ageing subjects [Seidman et al, 2002b].…”
Section: Do Mitochondrial Mutations and Reactive Oxygen Species Contrmentioning
confidence: 99%
“…In preclinical studies NTFactor has been used to reduce age-related functional damage. Using rodents Seidman et al (2002) found that NTFactor prevented hearing loss associated with aging and shifted the threshold hearing from 35-40 dB in control, aged rodents to 13-17 dB. They also found that NTFactor preserved cochlear mitochondrial function and prevented aging-related mitochondrial DNA deletions found in the cochlear.…”
Section: Molecular Replacement Of Oxidized Membrane Components and Itmentioning
confidence: 95%
“…They also found that NTFactor preserved cochlear mitochondrial function and prevented aging-related mitochondrial DNA deletions found in the cochlear. Thus NTFactor was successful in preventing age-associated hearing loss and reducing mitochondrial damage and DNA deletions in rodents (Seidman et al 2002). In clinical studies Lipid Replacement Therapy has been used to reduce fatigue and protect cellular and mitochondrial membranes from oxidative damage by ROS/RNS (reviewed in Nicolson, 2003;2010).…”
Section: Molecular Replacement Of Oxidized Membrane Components and Itmentioning
confidence: 99%
“…Compelling evidence exists from experiments in the authors' laboratory demonstrating that aged rats supplemented with a diet rich in phosphatidylcholine have improved auditory sensitivity when compared with placebo-supplemented rats. Furthermore, study of the subjects' mitochondrial function reveals a statistically significant improvement in mitochondrial energy production in the treated groups compared with placebo (Seidman et al, [11]). …”
Section: Vitamin B 3 (Niacin)mentioning
confidence: 99%